ChemInform Abstract: Synthesis of 2‐Amino‐imidazo[4, 5‐b]pyridines. Issue 36 (15th August 2013) - Rosenberg, Adam J.; Williams, Theresa M.; Jordan, Abraham J.; Clark, Daniel A.
Abstract The presented approach is completely regioselective, procedurally simple, and provides rapid access to previously difficult to access moieties.